Effects of motivating to sustain commitment of the sales professionals - Sayanjit Guha (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
Motivation is an important tool which can have a significant impact to improve the performance of employees in any organization and in the current competitive world, employees' commitment is crucial in achieving the organizational goals. The current research is aimed at examining the role played by motivation in sustaining the commitment of sales professionals. Primary data has been collected among 100 sales professionals using the close-ended questionnaire. For the analysis purpose both descriptive and inferential analysis has been conducted. The findings from the analysis show that most factors included in the model to measure the motivation show a signifi cant and positive impact. Similarly the coefficient for organizational support, psychological support and financial support shows a positive and significant impact. In examining the impact of increased motivation on employees' commitment, the results were also statistically significant and positive. On the basis of the findings it can be concluded that the motivation has a significant and positive impact on employees' commitment so organizations should focus on motivating their employees; however, the method used for motivation can differ from one organization to another.
Keywords: M10; M12; M14; M19; M50; M54; M59; 650; motivation; employee commitment; sales professionals; organizational support; financial support; psychological support